EUROPEANISATION OF THE MACEDONIAN PRIVATE INTERNATIONAL LAW – LEGAL EVOLUTION OF A NATIONAL PRIVATE INTERNATIONAL LAW ACT - Rumenov, Ilija (Faculty of Law Osijek Stjepana Radica 13 31000 Osijek, 2020)
The new Private International Law Act of the Republic of North Macedonia (hereinafter the PIL Act 2020) has been adopted in 2020. It represents one of the most comprehensive codification of European Union private international law (hereinafter the EU PIL) provisions in national private international law act. The PIL act 2020 implements most of the EU conflict of law rules and EU jurisdictional criteria especially those that have universal application. The most significant characteristics of PILA 2020 are: firstly, the act has limited the exclusive jurisdictional criteria; secondly, it introduced habitual residence as one of the main jurisdictional and conflict of law criteria; and thirdly, the act ‘mirrors’ the provisions that are present in the EU regulations. Moreover the PILA 2020 has positioned direct link between the decisions of the Court of Justice of the European Union regarding the EU PIL Regulations and the national courts, although N. Macedonia is still a candidate country to the EU. This Europeanisation of the Macedonian PIL has been done for two reasons: first, to modernize the rules in line with the new PIL trends, and secondly to prepare the Macedonian judges for the forthcoming radical change in the PIL when N. Macedonia becomes a full member in the EU. The intention of this article is not to give full detailed analyses of every provision in the new PILA 2020 but rather to provide for general overview of the solutions present in this act, as well to determine the main principles and new tendencies that would define the Macedonian private international law in future.
Keywords: Private International Law; Private International Law Act of the Republic of North Macedonia; Conflict of Laws; International Jurisdiction; Recognition and Enforcement of Foreign Judicial Decisions